Solubility of argon and nitrogen in aqueous solutions of tetradecyltrimethylammonium bromide from 283.15 to 298.15 K and 101,325 Pa partial pressure of gas (2017)
This paper reports experimental results regarding the solubility of argon and nitrogen in aqueous solutions of tetradecyltrimethylammonium bromide (TTAB) at temperatures between 283.15 and 298.15 K, 101,325 Pa partial pressure of gas, and 0.04–0.20 mol kg-1 of TTAB concentration. Measurements were taken in specially developed equipment, following the change in gas pressure. The gas solubility was determined applying Henry’s law. The experimental results show that the solubility of argon and nitrogen in theTTABmicelles is 62.5–86.3 times higher than the solubility in pure water. The solubility of the studied gases is larger in the TTAB micelles than in the DTAB determined in a previous work under the same experimental conditions, showing the effect of the addition of a methylene group in the alkyl chain of DTAB. Comparing the results obtained, it can be observed that the TTAB micelles are larger and have a higher solubilization capacity.